(De)Constructing the Self and Other in Veer Zaara - Shuri Mariasih Gietty Tambunan (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2019)
Films as cultural texts articulate the politics of everyday lives and one of the issues often depicted is on nationalism. The chosen case study for this article is Veer Zaara (2004), a romantic Bollywood movie telling us the story of two lovers from India and Pakistan who have to undergone multiple challenges to be together. The conflicts represent the ongoing and completely unresolved sibling rivalry between the two countries particularly after the partition in 1947. The main research question is how the film depicts the process of self-identification from the Indian characters by looking at the “cultural similarities and differences” compared to the Pakistani character while representing the effort of drawing a boundary between India and Pakistan? Research findings who that there are three dominant representational elements (space, religion and gender) in which the film with its authority select what forms of representation it would present concerning each country. In doing so, the film is making sure that India is identifying itself as a nation which is different from Pakistan or by drawing the boundary of India as the self and Pakistan as the other.